Effect of sulfur-fumigation process on ginseng: Metabolism and absorption evidences. (28th June 2020) - Shen, Hong; Zhang, Li; Xu, Jin-Di; Ding, Yong-Fang; Zhou, Jing; Wu, Jie; Zhang, Wei; Mao, Qian; Liu, Li-Fang; Zhu, He; Li, Song-Lin
Abstract: Ethnopharmacological relevance: Sulfur-fumigation has been developed to prevent insects and molds during post-harvest handling of Panax ginseng C.A. Mey (ginseng) in the near decades. Our previous study indicated sulfur-fumigation could transform ginsenosides, the active components of ginseng, into sulfur-containing derivatives (SFCDs), the artifacts with unknown toxicity. However, whether the biotransformation could be occurred and absorption characteristics between ginsenosides and SFCDs are still needed to further investigate. Aim of the study: To evaluate the effect of sulfur-fumigation process on ginseng through comparing the metabolic profile and absorption characteristics between ginsenoside Rg1, Re and their SFCDs. Materials and methods: Intestinal microflora and liver S9 fraction were utilized to compare the metabolic profile, and single-pass intestinal perfusion and Caco-2 cell models were applied to compare the absorption characteristics, between Rg1, Re and their SFCDs. Results: Rg1 and Re were metabolized to 7 none sulfur-containing metabolites, while their SFCDs were metabolized to 18 sulfur-containing metabolites. The intestinal absorption and transport of Rg1 and Re were much greater than their SFCDs. Besides, the uptakes of Rg1 and Re were transport-dependent, but their SFCDs were non-transport-dependent. Conclusion: Ginsenosides and their SFCDs could not be bio-transformed with each other and their absorption characteristics were quite different, which suggested that sulfur-fumigation is not a feasible post-harvest process of ginseng. Graphical abstract: Image 1